The petition in the Court of Session in early modern Scotland. (2nd September 2018) - Finlay, John
ABSTRACT: Petitions to Scotland's central civil court, the Court of Session, contained common features of style despite being presented for a wide range of purposes. As well as being employed in the course of procedure in a number of litigated cases, the petition was used to obtain entry to an office, or in seeking an equitable remedy which might relieve imminent suffering. In many cases they offer detailed narratives about everyday life, commerce, politics and religion which preserve a great deal that may be of value to the legal and social historian. Some petitioners, such as the poor and vulnerable, enjoyed a privileged status entitling them to have their claims heard summarily. A number of petitions, written by lawyers in order to persuade, contain ideas about liberty, justice and reason reflecting the fact that they were addressed to a court of both law and equity. This contribution identifies the features of such petitions, attempts to classify them, and considers their wider historical significance.